Awake Mouse Imaging: From Two-Photon Microscopy to Blood Oxygen Level–Dependent Functional Magnetic Resonance Imaging - Desjardins, Michèle; Kılıç, Kıvılcım; Thunemann, Martin; Mateo, Celine; Holland, Dominic; Ferri, Christopher G.L.; Cremonesi, Jonathan A.; Li, Baoqiang; Cheng, Qun; Weldy, Kimberly L.; Saisan, Payam A.; Kleinfeld, David; et al. (Biological psychiatry : cognitive neuroscience and neuroimaging, 2019)
Functional magnetic resonance imaging (fMRI) in awake behaving mice is well positioned to bridge the detailed cellular-level view of brain activity, which has become available owing to recent advances in microscopic optical imaging and genetics, to the macroscopic scale of human noninvasive observables. However, though microscopic (e.g., two-photon imaging) studies in behaving mice have become a reality in many laboratories, awake mouse fMRI remains a challenge. Owing to variability in behavior among animals, performing all types of measurements within the same subject is highly desirable and can lead to higher scientific rigor. We demonstrated blood oxygenation level–dependent fMRI in awake mice implanted with long-term cranial windows that allowed optical access for microscopic imaging modalities and optogenetic stimulation. We started with two-photon imaging of single-vessel diameter changes (n = 1). Next, we implemented intrinsic optical imaging of blood oxygenation and flow combined with laser speckle imaging of blood flow obtaining a mesoscopic picture of the hemodynamic response (n = 16). Then we obtained corresponding blood oxygenation level–dependent fMRI data (n = 5). All measurements could be performed in the same mice in response to identical sensory and optogenetic stimuli. The cranial window did not deteriorate the quality of fMRI and allowed alternation between imaging modalities in each subject. This report provides a proof of feasibility for multiscale imaging approaches in awake mice. In the future, this protocol could be extended to include complex cognitive behaviors translatable to humans, such as sensory discrimination or attention.